Group Exhibition-2008 OPEN 2008, 11th International Exhibition of Sculptures and Installations, Lido, Venice, Italy - Antoniou, Klitsa (My University, 2026)
2008 OPEN 2008, 11th International Exhibition of Sculptures and Installations, Lido, Venice, Italy Curated by Paolo De Grantis